Cytoplasmic replication of Staphylococcus aureus upon phagosomal escape triggered by phenol‐soluble modulin α. (12th November 2013) - Grosz, Magdalena; Kolter, Julia; Paprotka, Kerstin; Winkler, Ann‐Cathrin; Schäfer, Daniel; Chatterjee, Som Subra; Geiger, Tobias; Wolz, Christiane; Ohlsen, Knut; Otto, Michael; Rudel, Thomas; Sinha, Bhanu; et al.
Summary S taphylococcus aureus is a Gram‐positive human pathogen that is readily internalized by professional phagocytes such as macrophages and neutrophils but also by non‐professional phagocytes such as epithelial or endothelial cells. Intracellular bacteria have been proposed to play a role in evasion of the innate immune system and may also lead to dissemination within migrating phagocytes. Further, S. aureus efficiently lyses host cells with a battery of cytolytic toxins. Recently, phenol‐soluble modulins (PSM) have been identified to comprise a genus‐specific family of cytolytic peptides. Of these the PSMα peptides have been implicated in killing polymorphonuclear leucocytes after phagocytosis. We questioned if the peptides were active in destroying endosomal membranes to avoid lysosomal killing of the pathogen and monitored integrity of infected host cell endosomes by measuring the acidity of the intracellular bacterial microenvironment via flow cytometry and by a reporter recruitment technique. Isogenic mutants of the methicillin‐resistant S. aureus (MRSA) strains USA300 LAC, USA400 MW2 as well as the strongly cytolytic methicillin‐sensitive strain 6850 were compared with their respective wild type strains. In all three genetic backgrounds, PSMα mutants were unable to escape from phagosomes in non‐professional (293, HeLa, EAhy.926) and professional phagocytes (THP‐1), whereas mutants in PSMβ and δ‐toxin as well as β‐toxin, phosphatidyl inositol‐dependent phospholipase C and Panton Valentine leucotoxin escaped with efficiencies of the parental strains. S. aureus replicated intracellularly only in presence of a functional PSMα operon thereby illustrating that bacteria grow in the host cell cytoplasm upon phagosomal escape.